The Effect of Capital Market Education Program on Sharia Investment Literacy: An Empirical Study of Students and College Students in Wonogiri - Dwi Mahdani Cahya; Devina Melinawati; Makhda Intan Sanusi (Proceeding of the International Conference on Economics, Accounting, and Taxation, 2026)
This study aims to analyze the effect of a capital market education program on Sharia investment literacy among students and college students in Wonogiri Regency. The research background is based on the low level of financial literacy among young people and the vulnerability of Generation Z to illegal investment practices. This study used a quantitative approach with linear regression analysis. Data were collected through questionnaires distributed to 80 respondents who participated in the STAIMAS Wonogiri Investment Gallery education program. The instrument testing results showed that all items were valid and reliable, with Cronbach’s Alpha values of 0.892 for the education variable (X) and 0.873 for the investment literacy variable (Y). The results indicate that the Capital Market Education Program has a positive and significant effect on Sharia Investment Literacy, with a significance value of 0.000 (<0.05) and a t-test value of 8.676. The coefficient of determination (R²) shows that the education program contributes 49.1% to investment literacy improvement, while 50.9% is influenced by other factors. This study concludes that structured financial education effectively equips the younger generation with investment knowledge aligned with Sharia principles.